Rearing of brine shrimp, Artemia parthenogenetica using rice bran supplemented with fermented yeast - Immanuel, G (Indian Journal of Fisheries, 2011)
The suitability of rearing Artemia partitenogenetica (KKT 1) fed with rice bran supplemented with fermented yeast at 80 ppt salinity was studied. Feeding experiments were conducted to determine the survival, growth and reproductive traits of A. parthenogelWtica using different combinations of rice bran: yeast (1:1, 1:2, 1:3 and 1:4) with yeast fermented either in coconut water (yeast - CW) or in boiled rice water (Yeast - BRW). A combination of rice bran and yeast - CW in the ratio 1:4 supported maximum survival of 88%, whereas 1:1 combination of rice bran with yeast - BRW supported maximum survival of 64.3%. Better growth was obtained in 1:2 combination of rice bran and Yeast - CW (10.0 Â± 0.3 mm), but it was in 1:4 combination of rice bran and Yeast - BRW (8.4 Â± 0.2 mm). The ratio 1:4 of rice bran and yeast derived from the two sources supported maximum life span of 37 to 38 days as well as more fecundity. This study revealed that the different combinations of rice bran and yeast influenced the life history traits of A. parthenogenetica.